2016
DOI: 10.1080/09546634.2016.1255307
|View full text |Cite
|
Sign up to set email alerts
|

Topical corticosteroid concerns from the clinicians’ perspective

Abstract: The majority of clinicians may have inaccurate knowledge of certain aspects of TCC and own concerns to use TCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…10,11 Rates of AEs and discontinuations due to TEAEs in this study were greatest in the first 12 weeks of HP/TAZ treatment and decreased over time; AE rates were lowest after 36 weeks of treatment, with individual TEAEs reported in two or fewer participants. Survey data indicate that concerns about AEs from TCS use are common among both patients and clinicians, 20,21 and contribute to non-adherence in up to 28% of patients. 20 As the study population after week 12 was enriched for participants that had achieved IGA score improvement, these decreasing AE rates over time suggest that treatment with HP/TAZ lotion may minimize safety concerns for patients, potentially contributing to improved long-term adherence.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Rates of AEs and discontinuations due to TEAEs in this study were greatest in the first 12 weeks of HP/TAZ treatment and decreased over time; AE rates were lowest after 36 weeks of treatment, with individual TEAEs reported in two or fewer participants. Survey data indicate that concerns about AEs from TCS use are common among both patients and clinicians, 20,21 and contribute to non-adherence in up to 28% of patients. 20 As the study population after week 12 was enriched for participants that had achieved IGA score improvement, these decreasing AE rates over time suggest that treatment with HP/TAZ lotion may minimize safety concerns for patients, potentially contributing to improved long-term adherence.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,16 These differences are due in part to variability in professionals' TCS knowledge as well as the professionals' own fears regarding the potential adverse effects of these treatments. 10,14,17,18 Patients are looking for information, [19][20][21][22][23][24][25][26][27][28] particularly about adverse effects. [29][30][31][32][33] However, studies have shown that physicians provide little information regarding pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…TCS phobia has been shown to improve with patients' education [7]. Physicians (non-dermatologists) have concerns about using TCS more than dermatologists [8]. Additionally, pharmacists (from France and Australia) have low levels of confidence regarding the use of TCS [9,10].…”
Section: Introductionmentioning
confidence: 99%